SUBSTITUSI DALAM PUISI KARYA CARL SANDBURG SUATU ANALISIS SINTAKSIS - WONGKAR, CHRISTI A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This skripsi is entitled Subtitutions in the Poems of Carl Sandburg; A Syntactical Analysis. Substitution is useful to avoid the repetition that makes a sentence too long or boring. It can also help the readers to understand the sentences correctly. The aims of this research are to identify, classify the kinds of substitutions and analyse their functions in the poems of Carl Sandburg. The writer uses descriptive method. There are three steps to finish this research. First step is preparation, the writer read the poems of Carl Sandburg to find out the data. Second step is data collection, the writer read again the poems to get more accurate data, coloring and underline them, write them on a piece of paper and then numbering the data. Third step is data analysis. In classifying and analyzing the data, the writer uses the theory of Aarts and Aarts (1982). The result of this research shows that there are 84 substitutions used in the poems of Carl Sandburg. There are five kinds of subtitutions but there were only four substitutions found in the poems, those are noun phrase, verb phrase, a clause and adverbial expressions of place and time. The functions of substitutions which found in this poems are 67 substitutions to replace noun phrase, 4 substitutions to replace verb phrase, 7 substitutions to replace clause and 6 substitutions to replace adverbial of time and place. Keywords: Substitutions; Poems of Carl Sandburg, Aarts and Aarts, Syntactical Analysis.